The Influence of Injection sGnRH+Domperidon by Different Dosage to Egg Quality and Hatching of Betok (Anabas testudineus) - Edy Saptono; Sukendi '; Nuraini ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research was conducted from Oktober to November 2014 at Fish Breeding and Hatchery Laboratory Fisheris and Marine Science Faculty of Riau University. It was aim to know the influence of sGnRH+Domperidon injection by different dosage to egg quality and hatching of betok. It the research experiment method was applied with four treatmens and tree replications. The treatment injection by fisiologis solution 0,9 %, injection by sGnRH+Domperidon 0,5 ml/kg. 0,7 ml/kg and 0,9 ml/kg weigh of fish. The result showed that treatment with different dosage of sGnRH+Domperidon provide a significant influence on total of latency time of spawning, eggs ovulation/g weight of fish, eggs diameter, fertilization, egg hatchability and survival rate of larval. The best result was got from 0,5 ml/kg dosage with latency time 6,49 hour, total eggs ovulated 212/g weight of fish, accretion diameter of egg 0,184 mm, egg fertilized 75,11 %, egg hatchability 78,09 % and survival rate of living larvae was 82,36 %.Water quality during experiment was always in good condition for living.Keyword : Anabas testudineus, sGnRH+Domperidon, Hatching